AUTHENTICITY OF FLAVOR IN JAPANESE CUISINE AT ICHIRIN RAMEN PENUIN BATAM - Jacklyn Liu,; Tito Pratama,; Wahyudi Ilham,; Dailami, Dailami (Journal of Innovation Research and Knowledge, 2025)
The increase of Japanese restaurants in Indonesia has raised questions about how to identify which restaurant that serve authentic taste of Japan, while many adapted to local preferences. This research purpose is to analyze the concept of authenticity in the context of operating a Japanese restaurants in Indonesia, along with the factors that made a Japanese restaurants being considered authentic in terms of taste. This research uses Ichirin Ramen Penuin Batam as a case study. This research is using qualitative method to analyze data, gathered through interviews with chefs and customers, direct observations of the food preparation process and the restaurants atmosphere. The results show how Ichirin Ramen Penuin Batam preserves authenticity through constructed balance between tradition and adaptation. Customers perceive authenticity not only through taste but also through presentation, service, and atmosphere, indicating that authenticity is a holistic experience rather than a fixed standard. The study highlights that Japanese restaurants abroad can sustain cultural credibility by balancing tradition at Batam.